(untitled) (Journal of the College of Basic Education, 2022)
The research aims to show the nature of the reality of the Iraqi economy and its distortions and imbalances in the economic structures in light of the single income of the federal budget, represented by those imbalances in the production structure, the state’s general budget, and the structure of foreign trade. Iraq depends in financing its federal budget on oil exports more than it depends on the rest Other Exports This is why the federal budget deficit and its improvement were linked to the amount of oil exports from Iraq to the countries of the world. The descriptive analysis approach was adopted, as well as the systems analysis approach. The research revealed the inconsistency between the different sectors contributing to the percentage of the gross domestic product, which showed the dependence of the rentier economy dependent on the oil sector in building the state’s general budget, in addition to the fact that the Iraqi economy is going through a state of recession that has greatly affected the spread of unemployment, the phenomenon of poverty and the deterioration of services in a way. Year . The research recommends diversifying the sources of the gross domestic product, as well as not relying on the oil sector and its exports for the sustainability of the state and its entity, and paying attention to agricultural and industrial activity because they have a major role in supplying the Iraqi economy.